IMPLEMENTASI METODE ACTIVITY BASED COSTING (ABC) DALAM MENENTUKAN TARIF SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) PADA INTEGRATED PRE-SCHOOL HUSNA BANJARBARU BERDASARKAN PERSPEKTIF KEUANGAN - Yanti, Sari; Yusri, Yusri (ANALISIS, 2024)
ABSTRACT Cost accounting is a field of accounting that tracks, records, and analyzes costs. In this case, the preschool education institution will certainly require costs or funding from student fees. The purpose of this study is to explain how to determine the cost of Husna Banjarbaru Integrated Pre-School Education Program that has been implemented so far and is also expected to know how to determine costs using the ABC (Activity Based Costing) method. Of course, the determination of user costs must be in line with the financial point of view to help manage company finances appropriately and effectively so that company finances are always stable. The analytical approach uses a descriptive method design to provide an overview of the problem solving. Data collection techniques used in this research include interviews, observations, documentation, and literature review. Data analysis techniques use quantitative and qualitative analysis. This research was conducted in Integrated Pre-School Husna Banjarbaru, Srikaya Street No. 21, Guntung Paikat Village, South Banjarbaru District. The results of this study show that the determination of tuition fees (SPP) in Integrated Pre-School Husna Banjarbaru is still using traditional methods and the calculation results still do not give an accurate picture of the cost of education. By using Activity Based Costing (ABC) based costing, it can be seen that the determination of tuition fees is more accurate.